Lesion to the vmPFC abolishes intentionality (mis)attribution in the Knobe effect - Francesca Starita; Luigi A. E. Degni; Daniela Dalbagno; Elisa Ciaramelli (Scientific Reports)
Abstract Understanding others’ intentions is crucial for effective social interaction; however, the psychophysiological and neural mechanisms that drive intentionality attribution remain elusive. The Knobe Effect refers to the tendency to attribute more intentionality to actions resulting in negative compared to positive side effects, even if side effects are unintentional in both cases. This bias has been associated with the emotional responses and moral judgments elicited by the negative valence of the side effects, but findings remain contradictory, and few studies have explored their neural bases. This study investigates the causal contribution of the ventromedial prefrontal cortex (vmPFC), a region subserving emotional processing and moral judgment, in the Knobe Effect. Participants with vmPFC lesions and healthy controls rated the intentionality and valence of scenarios involving negative or positive side effects. Additionally, they rated the morality of the side effects, the subjective emotional response experienced during scenario reading and had their electrodermal activity recorded. Results showed that vmPFC patients, unlike controls, attributed similar levels of intentionality to positive and negative side effects, thus lacking the expected Knobe Effect. This occurred despite preserved recognition of the valence of the side effects but was accompanied by blunted emotional responses to the side effects and altered moral judgments. These findings support the view that emotional responses and moral judgment are fundamental for the Knobe Effect in healthy adults, and highlight the causal role of the vmPFC in driving this ubiquitous human bias.